O emprego de animais na Revolução Federalista de 1893 (Revista de História Regional, 2023)
The paper investigates the use of animals in the civil war of 1893, also known as the Federalist Revolution, which took place in Rio Grande do Sul in the last decade of the 19th century. The hypothesis is that, due to the characteristics of the insurgency and the territory in which it was fought, the use of animals was fundamental both for the government and for the federalist revolutionaries. Publications by civil war chroniclers and memoirists, as well as press records from the time and military documents are used as a database. Examples are limited to the Campos de Cima da Serra region and, in particular, to the municipalities of Lagoa Vermelha and Vacaria. The article shows that the insurgency demanded the wide use of animals that already existed in the gaucho territory and with which the local populations had a close historical, cultural, economic and even martial connection. At the end of the war, there was a decrease in the herds of cattle, horses and mules, precisely the animals used in the conflict for feeding, transport and combat functions.